Evaluation of the antioxidant activity of novel south Indian plant Commelina forskaolii and its prospective anticancer activity in Hep G2 cells - Manikandan Vani Raju; Sasikala Sekar Meenakshi Kaniyur Chandrasekaran
Oxidative stress plays a part in the progression of cancer and various types of diseases by damaging the DNA. Generally, plants have high antioxidant potency so that they can reduce oxidative stress. Plants are found to be effective in treating various types of cancers because of their antioxidant property. Commelina forskaolii was used in the primitive ages to treat various diseases. This study evaluated the antioxidant and cytotoxic potential of the novel medicinal plant C. forskaoliifollowed by qualitative and quantitative phytochemical analysis. DPPH, ABTS and hydroxyl radical scavenging activity were used to determine the antioxidant potential. The HepG2 cell line was used to study anticancer activity because it is a widely used cell line to study hepatotoxicity and hepatocellular carcinoma. The plant showed favourable antioxidant activity by scavenging various radicals such as DPPH, ABTS and hydroxyl radicals due to the presence of phytochemicals such as alkaloids, flavonoids, glycosides, tannins and terpenoids. Compared to the other plant extracts, the aqueous extract was found to be more potent in scavenging free radicals. The plant showed cytotoxicity against the HepG2 cell lines. The medicinal plant C. forskaolii contains a variety of phytochemicals and has high antioxidant potential. The plant has a capacity to inhibit the growth of liver cancer cells.